RETRACTED: Quercetin Inhibits Tumorigenesis of Colorectal Cancer Through Downregulation of hsa_circ_0006990 - Chen, Bin; Wu, Linguangjin; Tang, Xiaoxia; Wang, Ting; Wang, Shuyun; Yu, Hongjie; Wan, Guangsheng; Xie, Manli; Zhang, Ruijuan; Xiao, Haijuan; Deng, Wanli (Frontiers in Pharmacology, 2022)
Background This study was intended to investigate the function of Quercetin in chemoresistant colorectal cancer (CRC) cells. In addition, this research aimed to explore the mechanism by which Quercetin regulates the malignant behavior of CRC cells. Methods To induce THP-1 cells into M2 tumor-associated macrophages (M2-TAMs), THP-1 cells were stimulated by PMA and IL-4. MDC staining was used to investigate the autophagy in M2-TAMs. Meanwhile, cell proliferation was tested by colony formation assay. In addition, wound healing and transwell assay were performed to detect the cell migration and invasion, respectively. Dual luciferase assay was used to investigate the correlation between hsa_circ_0006990 and miR-132-3p/miR-532-3p. Furthermore, mRNA and protein levels were detected by RT-qPCR and western blot, respectively. Results Quercetin suppressed autophagy of M2-TAMs. In addition, M2-TAMs significantly inhibited the apoptosis and promoted the proliferation of CRC cells, while this phenomenon was reversed by Quercetin. Meanwhile, the expression of hsa_circ_0006990 in CRC cells was decreased by M2-TAMs, while Quercetin reversed this phenomenon. Furthermore, overexpression of hsa_circ_0006990 significantly reversed the anti-tumor effect of Quercetin on CRC. Conclusion Quercetin inhibited the tumorigenesis of colorectal cancer cells through downregulation of hsa_circ_0006990. Thus, our study might shed new lights on exploring the new strategies against CRC.